Association Between Community Economic Distress and Receipt of Recommended Services Among Medicare Fee-for-Service Enrollees. - Weeks, Bill; Cao, Stacey Y.; Lester, Chris M.; Weinstein, James; Morden, Nancy E. (Journal of General Internal Medicine, 2018)
Abstract